Levels of Abstraction, Contrast and Paradox in Sawāneḥ by Ahmad Ghazali - Mehrdad Akbari Gandomani (مطالعات زبانی و بلاغی)
The school of Ahmad Ghazali, his beliefs and interpretations in the context of mysticism, have gained a special aspect of form and meaning. Ghazali's avoidance of directly and openly dealing with the field of mysticism, apart from the heterogeneity of the textual context of his works from other mystical works, has also caused ambiguity in the textual context. In the book of Ghazali's accidents, countless double confrontations can be seen at the surface level; however, due to the transformations that have occurred in the level of relationships and other levels related to them, the authority of the text of love stories has turned into a temporary and transitory situation. Therefore, at the level of deep construction, aligned with Derrida's logic, sometimes by deconstructing the strains of dual oppositions and transferring them, the levels of reality have been transformed into other levels of abstraction, and by creating new links between them, the arena of single meaning and certainty Meaning is challenged. This method has sometimes been associated with changing the value of signifiers, and sometimes by using both this and that style, instead of either this or that style (replacing difference instead of distinction), has caused the creation of a new level based on paradox. In the following article, after understanding terms such as: authority, familiar and foreign boundaries, difference and distinction, levels of abstraction, connection and difference, based on the descriptive-analytical method, the types of paradoxes in Ahmed Ghazali's accidents have been investigated.